2017
DOI: 10.1158/1541-7786.mcr-17-0016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Effects of Stromal-Selective Targeting by uPAR-Retargeted Oncolytic Virus in Breast Cancer

Abstract: The tumor microenvironment (TME) is a relevant target for novel biological therapies. MV-m-uPA and MV-h-uPA are fully retargeted, species-specific, oncolytic measles viruses (MVs) directed against murine or human urokinase receptor (PLAUR/uPAR), expressed in tumor and stromal cells. The effects of stromal selective targeting by uPAR retargeted MVs were investigated. In vitro infection, virus-induced GFP expression and cytotoxicity by MV-h-uPA and MV-m-uPA were demonstrated in human and murine cancer cells and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…Although both MV-GFP and MV-CD46-muPA induced inhibition of tumor cell proliferation and enhanced in vivo apoptosis, the magnitude of the proapoptotic effect was significantly higher in tumors treated by the dual targeted virus. The antistromal effects by MV-CD46-muPA further validate a previous report by our group, showing that single targeted, stromal specific MV-muPA (selectively targeting mouse uPAR) induces significant modulation of murine stromal pathways, such as angiogenesis, inflammatory networks, as well as indirect modulation of human cancer cell pathways [27]. In this report, we further characterized the in vivo MV oncolytic mechanisms by functional RPPA of tumors treated by the tumor vs. tumor and stromal targeted MV vectors.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although both MV-GFP and MV-CD46-muPA induced inhibition of tumor cell proliferation and enhanced in vivo apoptosis, the magnitude of the proapoptotic effect was significantly higher in tumors treated by the dual targeted virus. The antistromal effects by MV-CD46-muPA further validate a previous report by our group, showing that single targeted, stromal specific MV-muPA (selectively targeting mouse uPAR) induces significant modulation of murine stromal pathways, such as angiogenesis, inflammatory networks, as well as indirect modulation of human cancer cell pathways [27]. In this report, we further characterized the in vivo MV oncolytic mechanisms by functional RPPA of tumors treated by the tumor vs. tumor and stromal targeted MV vectors.…”
Section: Discussionsupporting
confidence: 86%
“…4). We have previously reported the in vivo effects of stromal targeted only (MV-muPA) MV vectors compared with tumor only targeted vectors in breast cancer models, showing measurable, but modest effects of stromal only in vivo targeting [27]. The improved in vivo effects were associated with increased tumor viral protein (MV-N) expression, as well as increased tumor cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further approaches use collagen-derived matrices or synthetically engineered polyethylene glycol (PEG)-based hydrogels ( Table 3 ). 9 , 47 , 48 Collagen is a well-known structural protein of the connective tissue, and can be selectively lysed by collagenase in cell culture to release cells from the collagen matrix. Hydrogels provide a three-dimensional scaffold that encapsulates the cells and makes nutrient exchange possible ( Figure 1B ).…”
Section: Culture Systems Utilizing Hydrogels In Oncolytic Virotherapymentioning
confidence: 99%
“…Supported by a mouse model, the authors concluded that stroma-selective targeting per se constituted an efficient treatment option, even though targeting both tumor and tumor stroma led to the strongest antitumor effect. 47 …”
Section: Culture Systems Utilizing Hydrogels In Oncolytic Virotherapymentioning
confidence: 99%